Current Management of Dengue in Adults: a Review - DMPUK, Ralapanawa; SAM, Kularatne (IIUM Medical Journal Malaysia, 2015)
Dengue infection ranks highly among new and newly emerging arthropod-borne viral diseases affecting humans. It affects a large proportionof the population, mainly in tropical and sub-tropical countries, causing a high morbidity and mortality due to rising incidence of dengue haemorrhagic fever. The rapidly expanding global footprint of dengue is a public health challenge with a high economic burden.Appropriate management of the burden of dengue is hindered by several issues,including lack of understanding of the exact pathophysiology of the disease, failure to control the vector population effectively,lack of specific treatment for the disease, and technical obstacles in developing a vaccine. This review provides an overview on the epidemiology, natural history and management strategies of adult dengue patients.